A Predictive Model of Buying Intentions Based on Product Attributes and Geographical Factors: A Case Study in Pabean Market Surabaya - M. Azizul Khakim (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The objective of this research is to experimentally investigate the impact of product diversity, product quality, price, and location on consumer purchasing interest in a traditional market, namely Pasar Pabean Surabaya. The study utilized quantitative, correlational methodology through a survey method. Data was gathered from 40 consumers. The instrument utilized was a Likert-scale questionnaire, and the analysis employed multiple linear regression via SPSS 25. The results show that all four independent variables significantly affect purchase interest simultaneously and partially. Product quality dominates, followed by price and location. Although insignificant, product diversity has a significant impact. Purposive sample and contextual limitation to a particular traditional market may limit generalization. Quality of service, interaction with clients, and advertising strategies could be added to future studies. The findings suggest that market managers and local vendors should increase product quality, fair pricing, market accessibility, and product variety to attract and keep customers under current retail competition. This research contributes to the limited literature on consumer purchase behavior in traditional markets by integrating key marketing variables into a coherent statistical model.